The 'should' in conceptual engineering. Issue 8 (17th November 2018) - Simion, Mona
ABSTRACT: Several philosophers have inquired into the metaphysical limits of conceptual engineering: 'Can we engineer? And if so, to what extent?'. This paper is not concerned with answering these questions. It does concern itself, however, with the limits of conceptual engineering, albeit in a largely unexplored sense: it cares about the normative, rather than about the metaphysical limits thereof. I first defend an optimistic claim: I argue that the ameliorative project has, so far, been too modest; there is little value theoretic reason to restrict the project to remedying deficient representational devices, rather than go on a more ambitious quest: conceptual improvement. That being said, I also identify a limitation to the optimistic claim: I show that the 'should' in ameliorative projects suffers from a 'wrong-kind-of-reasons' problem. Last but not least, I sketch a proposal of normative constraining meant to address both the above results. The proposal gives primacy to epistemic constraints: accordingly, a concept should be ameliorated only insofar as this does not translate into epistemic loss.